Antecedents of Human Resource Competitiveness and Employee Performance and Their Influence on Organizational Performance Among Regional Contract Workers in East Kutai Regency Mediated by Education Level, Skills, and Work Relationships - Ausy Riana; Djoko Setyadi; Irwansyah Irwansyah; Ariesta Heksarini (Green Publisher Indonesia, 2025)
This research was conducted in East Kutai Regency, East Kalimantan Province, aiming to examine the influence of human resource competitiveness on the welfare of regional contract workers (TK2D). It also compares which mediation variables—education level, skills, or relationships between TK2D and superiors—most dominantly affect their welfare. The study’s title reflects its practical focus on current issues. The research uses a Mixed Method approach with an explanatory sequential design, combining quantitative and qualitative methods conducted in two stages. It also incorporates exploratory and experimental research types. Stratified sampling selected 379 regional contract workers as respondents. Structural Equation Modeling (SEM) analysis was performed with WarpPLS 6.0 software. Findings show that skills and employment relations significantly influence HR competitiveness (p<0.05), while education level has an insignificant effect. Employee performance is negatively influenced by skills but positively by organizational aspects. Organizational performance is significantly affected by education level and employee performance (p<0.05). The model explains 76.1% of HR competitiveness variance, 2% of employee performance variance, and 41.7% of organizational performance variance. These results highlight the importance of prioritizing skills development and improving employment relations in regional government policies to enhance both individual welfare and organizational performance within the public sector.